The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1111/j.1937-5956.2012.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Financing in a Distribution Channel with Capital Constraint

Abstract: T here exist capital constraints in many distribution channels. We examine a channel consisting of one manufacturer and one retailer, where the retailer is capital constrained. The retailer may fund its business by borrowing credit either from a competitive bank market or from the manufacturer, provided the latter is willing to lend. When only one credit type (either bank or trade credit) is viable, we show that trade credit financing generally charges a higher wholesale price and thus becomes less attractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
246
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 324 publications
(284 citation statements)
references
References 26 publications
13
246
0
2
Order By: Relevance
“…Jing et al [14] found that the overall supply chain efficiency under trade credit financing is higher than that under bank credit financing when production cost is low. However, our result shows that the trade credit financing cannot effectively increase the supply chain's efficiency under a low-carbon environment.…”
Section: Theoremmentioning
confidence: 99%
“…Jing et al [14] found that the overall supply chain efficiency under trade credit financing is higher than that under bank credit financing when production cost is low. However, our result shows that the trade credit financing cannot effectively increase the supply chain's efficiency under a low-carbon environment.…”
Section: Theoremmentioning
confidence: 99%
“…As an integrated part of a supply chain contract, trade credit can act as a risk-sharing mechanism among supply chain members [17]. Jing et al [18] compared the efficiency between bank credit financing and trade credit financing for a capital-constrained retailer and found that trade credit financing becomes highly effective when production cost is relatively low. Chen [19] further studied the coordination problem in the supply chain.…”
Section: Interface Of Operations and Financing Decisionsmentioning
confidence: 99%
“…Chen and Wang (2012) investigate the impacts of limited liability for the performance of SCF and shows that limited liability accounts for the reason why the retailer with a lower initial budget initiates a higher ordering level under trade credit contract [3]. Jing et al, (2012) discuss the equilibrium in SCF with two credit choices (bank or trade credit) and show that bank credit financing generally charges a lower wholesale price and thus becomes more attractive than trade credit financing for the retailer [4]. Zhang (2011) considered a multi-product newsboy problem with both supplier quantity discounts and a budget constraint.…”
Section: Introductionmentioning
confidence: 99%
“…Following the convention in the bank credit literature, we assume the bank market is competitive and that the risk-neutral banks have access to unlimited funds at the risk-free interest rate f R , which is normalized to zero without loss of generality [4], [8], [9]. We also consider the perfect capital market without taxes, transaction costs and bankruptcy costs.…”
Section: Model Descriptionmentioning
confidence: 99%